2015
DOI: 10.1177/1534735415588930
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Inhibits Invasiveness and Epithelial-Mesenchymal Transition in Oral Squamous Cell Carcinoma Through Reducing Matrix Metalloproteinase 2, 9 and Modulating p53-E-Cadherin Pathway

Abstract: Hypotheses. Epithelial-mesenchymal transition (EMT) and invasion play a critical role in cancer progression and metastasis. We have shown that low E-cadherin and high Twist expression are significantly correlated with prognostic survival prediction in oral squamous cell carcinoma (OSCC). This study aimed to determine the anti-invasive effect of curcumin on the expression of matrix metalloproteinases (MMPs) and of EMT regulators in OSCC. Methods. SCC-25 cells were treated with curcumin, and cell proliferation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 46 publications
2
59
0
Order By: Relevance
“…The effect of curcumin in decreasing MMP-2 and MMP-9 expression levels was reported in cancer cells, such as squamous cell carcinoma and osteoclastoma (Cao et al , 2015, Lee et al , 2015). Additionally, in vivo studies in humans and animals demonstrated curcumin’s effectiveness in decreasing the severity of periodontal diseases (Elburki et al , 2014, Nagasri et al , 2015, Bakir et al , 2016, Elburki et al , 2016).…”
Section: Discussionmentioning
confidence: 94%
“…The effect of curcumin in decreasing MMP-2 and MMP-9 expression levels was reported in cancer cells, such as squamous cell carcinoma and osteoclastoma (Cao et al , 2015, Lee et al , 2015). Additionally, in vivo studies in humans and animals demonstrated curcumin’s effectiveness in decreasing the severity of periodontal diseases (Elburki et al , 2014, Nagasri et al , 2015, Bakir et al , 2016, Elburki et al , 2016).…”
Section: Discussionmentioning
confidence: 94%
“…As higher doses of curcumin are related to impairment of the proliferation process of tumor cells (Lee et al, ), we analyzed the effects of lower doses of curcumin in normal and OSCC cell lines with different levels of differentiation and aggressiveness. We used keratinocytes (HACAT), high (CAL27) and low (SCC25) differentiated OSCCs, and fibroblast (NIH‐3T3), which were incubated with different doses of curcumin (2, 5, 10, 20, 30, 40, and 50 μM) for 24 h and then submitted to a proliferation assay (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The reported activity of curcumin against gastrointestinal cancers, breast cancer, ovarian cancer, head and neck squamous cell carcinoma, and lung cancer reflects its ability to affect multiple targets (Anand et al, ; Chen et al, ). Moreover, it has been found that curcumin inhibits oral cancer cell growth (Liao et al, ; Lee et al, ). However, these studies use variable curcumin concentrations (1–200 μM), and in most of them, the dosages used are usually higher than the ones that we used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Among MMPs, MMP-2 (gelatinase A) and MMP-9 (gelatinase B) are vital enzymes involved in the degradation of gelatin, collagen and laminin, main components of ECM [9] and high expressions of them are indicators of high invasive potential of cancer cells and are related to poor prognosis of patients [3, 10, 11]. In contrast, down-regulation of MMP-2 and MMP-9 provides a preventive measure against tumor metastasis [12, 13]. Additionally, the 5′ end of promoter region of the MMP-2 and MMP-9 gene contains a variety of regulatory sequences that binds well-characterized transcriptional units of MMP-2 and MMP-9, including nuclear factor-kappa B (NF-κB), SP-1, cAMP response element-binding protein (CREB), and activator protein (AP)-1, possibly contributing to tumor metastasis [14, 15].…”
Section: Introductionmentioning
confidence: 99%